1989
DOI: 10.1007/bf00439454
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral muscarinic actions of physostigmine and oxotremorine on avoidance responding of squirrel monkeys

Abstract: The involvement of central and peripheral muscarinic cholinergic receptors in the behavioral effects of the cholinesterase inhibitor physostigmine was evaluated by comparing the ability of atropine and methylatropine to reverse the effects of physostigmine, the muscarinic agonist oxotremorine, or their quaternary analogs neostigmine and oxotremorine-M. Avoidance behavior was maintained under a schedule in which every lever press postponed delivery of electric shock for 20 s; shock occurred every 5 s in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Indeed, these longer delays, where performance was poor, were included precisely because we wished to maximize the likelihood of detecting any improvements in performance; had disruptions been expected, then shorter delays would have been appropriate -as in the Dunnett (1985) study on enhancement/disruption following cholinergic stimulation and blockade respectively. The finding that both OXO and THA adversely affected latency and response rates agrees with Witkin's (1989) report that OXO and the anticholinesterase physostigmine decrease response rates in squirrel monkeys. However NIC, at the doses used here, had no measurable effect on these measures.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, these longer delays, where performance was poor, were included precisely because we wished to maximize the likelihood of detecting any improvements in performance; had disruptions been expected, then shorter delays would have been appropriate -as in the Dunnett (1985) study on enhancement/disruption following cholinergic stimulation and blockade respectively. The finding that both OXO and THA adversely affected latency and response rates agrees with Witkin's (1989) report that OXO and the anticholinesterase physostigmine decrease response rates in squirrel monkeys. However NIC, at the doses used here, had no measurable effect on these measures.…”
Section: Discussionsupporting
confidence: 88%
“…Since previous studies have demonstrated that stimulating muscarinic AChRs improves and blocking them impairs WM performance (Cools and Arnsten 2021;Liu et al 2017;Sarter and Lustig 2019; Thiele and Bellgrove 2018), we expected changes in foraging behavior after administration of muscarinic AChR agonist and antagonist. However, we failed to find any significant effect on WM parameters, even though the same dosages of drugs significantly altered WM performance in previous studies (Vardigan et al 2015;Witkin 1989). This negative result may simply be due to differences in behavioral tasks, as nicotine has a greater effect in more difficult WM tasks (Katner et al 2004).…”
Section: Effects Of Muscarinic Achr Agonist and Antagonistcontrasting
confidence: 95%
“…One monkey (N) was tested for the agonist and antagonist of nicotinic AChR only. The dosage of each drug was determined based on previous pharmacological experiments in monkeys (Katner et al 2004;Vardigan et al 2015;Witkin 1989). The injection volume was 1.0 mL for all experiments.…”
Section: Procedures Of Pharmacological Experimentsmentioning
confidence: 99%
“…To assess whether such probe‐dependence was manifest at the mouse M 4 mAChR, we performed additional functional interaction studies with two other orthosteric mAChR agonists, oxotremorine and xanomeline. The former agent was chosen because it is centrally active and often used for in vivo studies of mAChR function (Witkin, 1989; Chan et al ., 2008); the latter agent was chosen because it is M 1 /M 4 mAChR‐preferring and, as indicated in the Introduction, has shown clinical efficacy in reducing positive, negative and cognitive indices associated with schizophrenia. Figure 3 summarizes the results of these experiments, where it can be seen that substantially different degrees of potentiation were noted depending on whether the agonist was oxotremorine (Figure 3A) or xanomeline (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%